MO753: Marinobufagenin Predicts Intradialytic Hypotension Episodes in Prevalent Haemodialysis Patients. (3rd May 2022) - Carullo, Nazareno; Greco, Marta; Presta, Pierangela; De Rosa, Salvatore; Crugliano, Giuseppina; Sabatino, Jolanda; Arena, Roberta; Andreucci, Michele; Indolfi, Ciro; Foti, Daniela; Coppolino, Giuseppe; Bolignano, Davide
Abstract: BACKGROUND AND AIMS: Intradialytic hypotension (IDH) is a sudden and often dangerous complication of chronic haemodialysis (HD) treatment that may occur in ∼20%–30% of HD sessions. The pathogenesis of IDH is acknowledged to be multifactorial, as it might depend from an impaired vascular refilling capacity, excessive absolute fluid removal, an impaired sympathetic nerve response to volume loss or inadequate peripheral arterial vasoconstriction. This makes the prediction of IDH extremely challenging in the majority of cases. METHOD: In this pilot, prospective study, we aimed at evaluating the clinical predictors of IDH in a small cohort of prevalent HD patients, with a particular focus on marinobufagenin (MBG), an endogenous cardiotonic steroid whose blood levels have previously been found notably altered in various cardiovascular disorders and body fluid status alterations. RESULTS: MBG levels in HD patients were significantly higher than in controls (0.75 ± 0.29 versus 0.59 ± 0.19 nnmol/L; P = 0.03), remained unchanged throughout a single HD session and were not correlated with the absolute or partial fluid loss achieved. During a 30-day follow-up, 19 patients (65.5%) experienced at least one IDH (73 total episodes). An inverse correlation was found between baseline MBG and the number of IDH ( R = –0.55; P = 0.001). HD patients experiencing IDH presented remarkably lower baseline MBG as compared with others (0.65 ± 0.28 versus 0.94 ± 0.21 nmol/L; P = 0.008) In these individuals, there was an apparent increase in MBG levels after the first hour of dialysis [0.72 (0.56–1.00) versus 0.65 ± 0.28 nmol/L; P = 0.04], while such levels progressively decreased throughout the rest of the session, being even more reduced at HD end as compared with baseline [0.45 (0.24–0.95) versus 0.65 ± 0.28 nmol/L; P = 0.04]. At Kaplan–Meier analyses, HD patients with lower MBG manifested a 4-fold to6-fold increased risk of IDH during follow-up (crude HR ranging from 4.37 to 6.68), depending on the time-point measurement of MBG. At Cox regression analyses, MBG measured at different time points resulted the strongest time-dependent predictor of IDH among all the variables considered (HR ranging from 0.068 to 0.155; P=0.002 to <0.0001). CONCLUSION: Findings obtained suggest that altered MBG in prevalent HD patients may reflect a diverse vascular and haemodynamic tolerance to HD stress, eventually leading to recurrent IDH episodes. Further studies are needed to confirm the prognostic capacity of MBG for identifying HD patients at high risk of IDH, particularly those with apparently optimal fluid status.